EXPLORING THE RELATIONSHIPS AMONG PHYSICAL ACTIVITY, TYPE 2 DIABETES, AND VITAMIN D: INSIGHTS FROM A CROSS-SECTIONAL STUDY (The Research of Medical Science Review, 2025)
Introduction: Globally, diabetes mellitus and obesity are rising due to poor adaptive lifestyle factors like unhealthy diet, higher BMI and physical inactivity, which is the main cause of metabolic syndrome. Daily physical activity can reduce the risk of developing Type 2 diabetes, cardiovascular diseases and severe comorbidities. Methodology: A sample of 200 type 2 diabetic patients was chosen from the Endocrinology Ward at Lady Reading Hospital (LRH) in Peshawar based on written agreement. A self-made questionnaire was designed to collect information on demographics (age, gender, family medical history and education), anthropometrics (weight, height and BMI), biochemical (HbA1c, lipid Profile and CRP) and a standard Global Physical Activity Questionnaire (GPAQ) was used. The descriptive and one-way ANOVA was used to assess the data through SPSS. Major Results: The participants were mostly male (52%), between the ages of 25 and 60, with illiterate (55%) and positive family history of hypertension, heart disease and diabetes. Females showed greater trends of overweight and obesity, with BMI (26.22 ± 5.37), but males typically maintained a normal weight. Glycemic control was inadequate both (9.59 ± 2.41) in males and (9.51 ± 1.76) females. Physical activity data from GPAQ analysis indicated that 30.8% of male respondents had jobs requiring standing or walking throughout the day, while most engaged in little to no physical activity such as walking, cycling, or household chores. Among females, 86.5% were housewives, with most not participating in structured physical activities like exercise, walking, or cycling, though the majority performed household chores for 1–3 hours daily. Overall, physical activity levels were low, with minimal involvement in regular exercise, walking, or recreational activities. Conclusion: The study showed poor glycemic control and limited physical activity, with females exhibiting higher obesity trends. Overall, sedentary lifestyles, poor education and a strong family history of diabetes indicate a high risk for metabolic disorders.